Has contract farming improved the green technology efficiency of vegetable growers? Empirical evidence from rural areas in Shandong Province, China - Qi Li; Zixuan Wang (Agricultural Economics (AGRICECON))
Contract farming is regarded as an effective strategy for smallholder farmers in developing countries to enhance their agricultural competitiveness. However, limited research exists on its potential to promote green, sustainable development. This paper investigates the impact of contract farming participation on farmers' green technology efficiency using data from a sample of 627 vegetable growers in Shandong, China and employs the propensity score matching method. Our findings are as follows: i) Under the counterfactual assumption, participation in contract farming increases green technology efficiency from 0.560 to 0.614. The efficiency of contract production bases, ranked from highest to lowest, is as follows: self-owned base, stock-sharing base, and contractual base. ii) The provision of productive services serves as a significant mediating factor in enhancing green technology efficiency, with a more substantial impact than issuing planned instructions. iii) Increasing purchase prices, as an effective means of providing motivational incentives, significantly amplifies the effect of contract farming on green technology efficiency in self-owned and stock-sharing bases. As organisational models evolve toward greater integration, the enhancing effect of price incentives on green technology efficiency strengthens. This study concludes with several public policy and agricultural management recommendations.